Prevalence and main outcomes of placenta accreta spectrum: a systematic review and meta-analysis - Jauniaux, Eric; Bunce, Catey; Grønbeck, Lene; Langhoff-Roos, Jens (American journal of obstetrics and gynecology, 2019)
The objective of this study was to evaluate the prevalence of placenta accreta spectrum in general population studies and the main maternal outcomes at delivery. We searched PubMed, Google Scholar, clinicalTrials.gov, and MEDLINE between 1982 and 2018. Articles that provided data on the number of cases of placenta accreta spectrum per pregnancies, births, or deliveries in a defined population were used. Study characteristics were evaluated by 2 independent reviewers who used a predesigned protocol. Primary outcomes were the prevalence of placenta accreta spectrum and clinical diagnostic data at birth; the pathologic criteria were used to confirm the diagnosis. Secondary outcomes included cases that required transfusion, incidence of peripartum hysterectomy, and maternal mortality rates. Heterogeneity between studies was analyzed with the Cochran’s Q-test and the I2 statistics. Of the 98 full-text studies that were identified, 29 articles met the defined criteria and included 22 retrospective and 7 prospective studies comprising 7001 cases of placenta accreta spectrum of 5,719,992 births. Prevalence rates ranged from 0.01–1.1% with an overall pooled prevalence of 0.17% (95% confidence interval, 0.14–0.19). Only 10 studies provided detailed histopathologic data. The pool prevalence for the adherent vs the invasive grades was 0.5 (95% confidence interval, 0.3–0.36) and 0.3 (95% confidence interval, 0.2–0.4) per 1000 births, respectively. The pooled incidence for peripartum hysterectomy was 52.2% (95% confidence interval, 38.3–66.4; I2=99.8%) and 46.9% (95 % confidence interval, 34–59.9; I2=98.8%) for hemorrhage that required transfusion. The pooled estimate of maternal death was 0.05% (95% confidence interval, 0.06–0.69; I2=73%). We found large amounts of heterogeneity between studies for all parameters and further quantification was limited because of methodologic inconsistencies between studies with regards to clinical criteria that were used for the diagnosis of the condition at birth and the histopathologic confirmation of the diagnosis and differential diagnosis between adherent and invasive accreta placentation. This meta-analysis indicated wide variation between studies for the prevalence rate of placenta accreta spectrum and for the different grades of accreta placentation that highlighted the need for consistency in definitions that are used to describe placenta accreta spectrum at birth and in the reporting of this increasing common obstetric complication.